The relationship between economic performance and energy consumption at EU level - Andrei Teofil Postolachi (CES Working Papers, 2023)
Starting from the premise that an increase in the use of energy determines a corresponding economic growth, this article aims to determine if at the community level of the European Union there is a causality between energy consumption and economic performance. Thus, using the multiple regression analysis, we sought to determine if, at the level of all 28 member states of the EU, the economic performance, measured through GDP, can be explained by the simultaneous variation in the consumption of the 5 types of primary energy: solid fuels, electricity, natural gas, oil and renewable energy. The results, of particular importance in the development of measures through the European energy policy, show a significant impact of the use of electricity, oil and renewable energy on the European GDP, while the influence of coal and natural gas consumption has a low intensity.
Keywords: 330; EU energy policy; economic performance; energy consumption; solid fuels; oil; naturalgas; electricity; renewable energy